THE EFFECT OF THE SCHOOL NUTRITION PROGRAM (NGTS) ON THE NUTRITIONAL STATUS OF PRIMARY SCHOOL STUDENTS IN CIMAHI CITY - Ramadhan, Winda Novita Ramadhan; Elvandari, Millayntri; Fitria, Mona; Priawantiputri, Witri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
As a form of support for the nutritional concerns of school-age children, SEAMEO RECFON initiated a flagship program for the development plan for the next five years called Nutrition Goes to School (NGTS). The study aims to see how the impact of the NGTS program on the nutritional status of elementary school students. This study used a cross sectional design. By using two sample groups, namely the school group that ran NGTS for two years and the Non-NGTS school group. Both sample groups have the same characteristics, namely private schools, and both are located in Cimahi city. Based on the results of sample determination, after conducting several sampling stages with quota sampling. Then obtained a minimum sample size of 100 students from each group with a total sample size in this study of 200 elementary school students. Furthermore, the data were tested with an independent t-test, the results showed that there was a significant difference between the mean value of nutritional status (IMT / U) in the school group with the NGTS program and the NGTS Non-Program with a p-value = 0,004 (p <0,005). These results are in line with the student nutritional status data found in this study, where undernutrition and overnutrition were much higher in Non-NGTS schools compared to NGTS schools. This shows that there is an effect of the NGTS program on the nutritional status of primary school students.